2
$\begingroup$

I am reading MIT PDF here: http://ocw.mit.edu/courses/mathematics/18-03sc-differential-equations-fall-2011/unit-ii-second-order-constant-coefficient-linear-equations/exponential-response/MIT18_03SCF11_s14_4btext.pdf

The 2nd question is enter image description here

and the solution is : enter image description here

My question is, how do they go from the complex form to the real form? Re(z), what is this operation.

Also, if the function had been a sin(t) instead of cos(t) in the ODE, then I would take Im(z), how do I do this operation aswell?

An example where that might apply is let's say x''+5'x+6x = sin(5t)

$\endgroup$
1
  • $\begingroup$ Welcome to math.stackexchange. This is a well-posed first question (you showed effort, nice screenshot, ...). Do no forget to accept an answer or ask for more information if it was still unclear. $\endgroup$
    – Pedro
    Mar 17, 2015 at 0:02

2 Answers 2

1
$\begingroup$

$Re(x)$ gives you the real part: $Re(x) = Re(a + bi) = cos(a)$

$Im(x)$ gives you the imagniary part: $Im(x) = Re(a + bi) = sin(b)$

In your example: $x_P = Re(z_p) = Re(\frac{te^{-t}( cos(t) + i sin(t) )}{2i}) = Re(\frac{te^{-t}cos(t)}{2i} + \frac{te^{-t}sin(t)}{2}) = Re(-\frac{ite^{-t}cos(t)}{2} + \frac{te^{-t}sin(t)}{2}) = \frac{te^{-t}sin(t)}{2}$

$Im(z_p) = Im(-\frac{ite^{-t}cos(t)}{2} + \frac{te^{-t}sin(t)}{2}) = -\frac{te^{-t}cos(t)}{2}$.

$\endgroup$
0
$\begingroup$

let us take the example you have. $$x'' + 5x' + 6x = \sin 5t.$$ then $$x = e^{\lambda t} $$ is a solution of the homogenous equation if $$\lambda^2 + 5 \lambda + 6 = 0 \to \lambda = \frac{-5 \pm \sqrt{1}}{2}=-2, -3$$ unfortunately, this equation has no complex roots.

let us try instead $$x'' + 4x' + 6x = \sin 5t.$$ the char equation is $$\lambda^2 + 4 \lambda + 6 = 0 \to \lambda = \frac{-4 \pm \sqrt{-8}}{2}=-2\pm\sqrt 2i$$

you can verify that both $$ x = e^{-2t}\cos\sqrt 2 t,\, x = e^{-2t}\cos\sqrt 2 t $$ satisfy the homogeneous equation.

these two solution can be thought as coming from the real and imaginary parts of $$e^{-2t + i\sqrt 2t} = e^{-2t}\left( \cos \sqrt 2 t + i \sin \sqrt 2 t\right).$$ i have used the eulers formula $e^{it} = \cos t + i \sin t.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.